Signifikansi Pemikiran Sayyid Abdullah Bin Alwi Al-Haddad Dalam Kitab Risalah Al-Muawanah Tentang Pendidikan Akhlak - Hidayati, Nur (LPPM, 2019)
Sayyid Abdullah bin Alwi Al-Haddad is a famous figure of Sufism. One of the books is the Minutes of Al-Mu'awanah, this study aims to find out how moral education according to Sayyid Abdullah Bin Alwi Al-Haddad in the Book of Al-Mu'awanah. The questions to be answered through this research are: (1) How is moral education according to Sayyid Abdullah bin Alwi Al-Haddad in the Book of Minutes of Al-Mu'awanah (2) What are the implications of the moral education of the Book of Al-Muawanah treatise according to Sayyid Abdullah bin Alwi Al- Haddad in everyday life. The research method used is library research. The data obtained is sourced from the literature. The primary data source is the Al-Mu'awanah Risalah, the secondary source is the translation and the other sources are the books and other books that are relevant and relevant to the research. The technical data analysis (content analysis) uses the Deductive method, the Inductive method. The findings of this study, show that the values ​​of moral education contained in the book of the Book of Al-Mu'awanah by Sayyid Abdullah bin Alwi Al-Haddad is very relevant to education now, and is needed to change students who are currently still madhmumah. ), be a person of morality (good). The model of moral education in the Book of Al-Mu'awanah is arguably very practical and still holds fast to the Qur'an and the Hadith. The thoughts of Sayyid Abdullah bin Alwi Al-Haddad about the moral education contained in the Book of Al-Mu'awanah can be grouped into three large-scale writers. First: Morals to Allah SWT. Second: Moral towards yourself. Third: Moral towards the environment